PERLINDUNGAN KERJA LAYAK PADA PEKERJAAN ASISTEN RUMAH TANGGA PEREMPUAN DI DESA SOCAH, BANGKALAN-MADURA - miftachul choir; anita kristina (Universitas Lancang Kuning, 2021)
The purpose of the study was to analyze the decent work protection of female domestic assistant workers. This research was conducted with a qualitative phenomenological approach, analyzed by the inductive method. Data collection was carried out by in-depth interviews with female household assistant actors and their employers in the village of Socah, Bangkalan-Madura. The findings show that there is work hour discrimination that is hours of work not in accordance with the initial agreement, there is workload discrimination that is doing a lot of work beyond the value limit of women, and findings on work protection without insurance. In the end it can be concluded, decent work is said to be socially feasible, because it is presented in work ethics. And discrimination against this work occurs a lot in social relations in the work of this female household assistant